Correlation of parasite density and biochemical parameters in children with malaria infection in Calabar, South-South Nigeria - Akpan Uwem Okon; Bassey Iya Eze; Uwaetteh Akanimoh Emmanuel; Inyang Wisdom Marcus; Usoro Chinyere Adanna (Egyptian Pediatric Association Gazette, 2022)
Abstract Background Malaria parasitemia is associated with premature, excessive hemolysis, induction of oxidative stress, and derangement in metabolism of iron, proteins, and some electrolytes. This study aims to evaluate the effects of malaria infection on ascorbic acid (AA), uric acid (UA), iron, transferrin, albumin, total iron-binding capacity (TIBC), calcium, and magnesium levels in malaria infection. Results Among the 50 malaria-infected children, 12 had severe parasitemia (PD ≥ 10,000 parasites/μl), 16 had moderate parasitemia (PD: 2000 to < 10,000 parasites/μl), and 22 children had mild parasitemia (PD < 2000 parasites/μl). The AA, iron, transferrin, and TIBC levels were significantly lower and UA and Mg higher in malaria-infected children compared with the controls. Ascorbic acid correlated negatively with UA and PD in malaria-infected children. Iron correlated positively with albumin, transferrin, and TIBC in malaria-infected children, while Ca correlated negatively with Mg levels. Conclusion Malaria infection in children is associated with reduced AA and iron parameters and increased UA and Mg levels; hence, vitamin C and iron supplementation could be useful in malaria therapy.